THE DEVELOPMENT OF INHERITANCE MODULE BASED ON KITAB ASASUL FARAID IN SENIOR HIGH SCHOOL - Robby, Muhammad Fadhli; Afifulloh, Mohammad; Sulistiono, Muhammad (Edukasi Islami: Jurnal Pendidikan Islam, 2025)
Bacground: Islamic Religious Education (PAI) is crucial for fostering students’ character and understanding of Islamic teachings, yet inheritance law remains challenging due to its abstract principles and complex calculations. This study developed a PAI module based on Kitab Asasul Faraid to enhance learning outcomes for senior high school students. Using a Research and Development (R&D) approach with the ADDIE model (Analyze, Design, Develop, Implement, Evaluate), the module was validated by two experts in Islamic studies and tested with 34 Grade XII students at SMAN 2 Kota Kediri. Results showed strong validity (92–96%), positive student feedback (76% rated it highly effective), and significant improvement in pre- and post-test scores (78 to 82; t = 14.3, p < 0.05). The module effectively improved students’ comprehension of inheritance law by integrating classical Islamic texts into accessible learning resources. It is recommended for broader adoption in high schools and adaptation for digital platforms to enhance accessibility. Conclusion: The main contribution of this research is to provide a learning model that can be used as a strategic alternative in the design of research curriculum in Islamic higher education, which is responsive to the needs of students and the challenges of the contemporary era.